2022
DOI: 10.1007/s12325-022-02160-y
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Repository Corticotropin Injection for the Treatment of Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder that affects multiple organ systems. The most prevalent manifestations include constitutional symptoms, arthritis, and rash. An SLE flare is defined as a measurable increase in disease activity that may prompt a change in treatment. According to the European Alliance of Associations for Rheumatology guidance, SLE treatments should be aimed at reducing disease activity and flares, as well as preventing organ damage. Standard-of-care treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…A narrative review found that pooled data from 3 clinical trials of SLE showed significant improvement of British Isles Lupus Assessment Group 2004 index scores after 8 weeks of Acthar therapy, and decreased tender and swollen joint counts after 4 weeks. Few serious AEs were reported in the trials and Acthar exhibited an acceptable safety profile [ 45 ].…”
Section: Clinical Studies Of Acthar: 2014–2022mentioning
confidence: 99%
“…A narrative review found that pooled data from 3 clinical trials of SLE showed significant improvement of British Isles Lupus Assessment Group 2004 index scores after 8 weeks of Acthar therapy, and decreased tender and swollen joint counts after 4 weeks. Few serious AEs were reported in the trials and Acthar exhibited an acceptable safety profile [ 45 ].…”
Section: Clinical Studies Of Acthar: 2014–2022mentioning
confidence: 99%